The Effects of Protected Feed Supplements on Estrus Response, Milk Production and Composition of Sapera Dairy Goats - Pramono, Dr. Ahmad; Muhammad, Muhammad; Riyadi, Fairuz Izzudin; Cahyadi, Muhammad (Buletin Peternakan, 2024)
Soybean groats and earthworms (Lumbricus rubellus) are natural sources of protein, which are easy to obtain. Therefore, this research aims to evaluate the effects of protected soybean groats (PSG) and earthworm meal (PEM) in the diet on estrus response, milk production and composition of Saanen Peranakan Etawa (Sapera) dairy goats. These feed supplements were further protected by 1% formaldehyde. A completely randomized design with three treatments consisting of basal diet (P0), 75% basal diet + 25% PSG (P1), and 74.96% basal diet +24.99% PSG and 0.05% PEM (P2) was used in this research. Also, a total of 21 lactating Sapera goats were utilized and equally grouped into these treatments. Milk productions and composition were recorded and checked using a Lactoscan milk analyzer. Moreover, estrus synchronization was applied using the PGF2α and GnRH hormone using the intramuscular (IM) injection method and observing estrus. The data were analyzed using one-way analysis of variance while the differentiation of treatments was conducted with Duncan's multiple range test (DMRT). Electrical current resistance, vaginal temperature, vulva color, milk production, fat, total solids, and protein contents were observed to be significantly affected by the supplementation of PSG and PEM (P<0.05). In conclusion, supplementation of PSG and PEM in the diet could improve estrus response, milk production and composition of Sapera goats.